Pregnancy beyond 65: report of a unique case and discussion of a controversial issue. (1st November 2016) - Simó González, Marta; Calaf Alsina, Joaquim; Terribas Sala, Núria; Luqui Scarcelli, Nerea; Plana Borrás, Juliana; Polo Ramos, Ana
Abstract: We present the case report of a 66-year-old woman who was attended at our gynaecology department at a tertiary university hospital in Barcelona, Spain for a high-risk pregnancy and comment on the obstetric implications and bioethical issues. We retrospectively analysed clinical data about the case and bibliographic references related to the issue. The woman underwent in vitro fertilisation of donated embryos in a private centre and came to our unit at 27 weeks of gestation for pregnancy care. At 33 weeks, she presented pre-eclampsia and a caesarean section was performed. She gave birth to healthy twin boys. Four months later, she returned to our centre with the diagnosis of ovarian cancer and died 30 months after delivery. We present the clinical course and management of this pregnancy and comment on the obstetric implications, the impact on maternal and neonatal health, and bioethical issues related to assisted reproduction techniques in pregnancies beyond the natural reproductive age.